Evaluación de Catalizadores en Vehículos de Encendido Provocado: Un Enfoque Multimodal utilizando Termografía Infrarroja y Emisiones Contaminantes - Rodríguez Ortiz, Leodán Alexander (2024)
This research aims to comprehensively explain the meticulously executed sequential process that determines the operational status of the catalyst in automobiles equipped with an otto duty cycle. This complex procedure entails a thorough examination of numerous factors that have a direct impact on the engine's efficiency and, consequently, the catalyst itself. These factors include, among others, the quality of the fuel used, the various engine operating modes, and the current mileage accumulated by each of the vehicles subjected to the experimental tests. We carry out the evaluation based on an experimental framework that meticulously defines the specific parameters crucial to the data collection process in the various tests. The use of thermographic imaging techniques complements this, facilitating the determination of catalyst operating temperatures and their responsiveness to various operating parameters, as well as measuring their contribution to the emission of harmful gases. After analysis using statistical programs, it is possible to determine to what extent these factors influence the resulting production variables. It is crucial to consider that factors beyond the purview of this study may impact the diagnostic process concerning the catalyst's condition. Keywords: catalyst, thermography, gas analyzer, polluting emission